Analysis of Urban Drainage System Based on Ponorogo City Spatial Planning - Setiyo, Anugrah Dwi; Nugroho, Laksono Djoko; Wulandari, Esti (Jurnal Teknik Indonesia, 2025)
The infrastructure problem in Ponorogo Regency is characterised by flooding in urban areas, which is attributable to deficiencies in the drainage system. The regions of Ponorogo City that are most susceptible to flooding include Jl. Pramuka, Jl. Jaksa Agung Suprapto, Jl. Bhayangkara, and Jl. Kbp Duriyat. The findings of the distribution suitability calculations for Ponorogo Rainfall Station over a period of 20 years demonstrate the validity of the calculations performed using the Log Pearson Type III method. Subsequently, the Normality Test was conducted in accordance with the Smirnov-Kolmogorov And Chi-Squared criteria. The Log Pearson Type III Method value was deemed to be acceptable. Consequently, the Log Pearson Type III Method was selected as the rainfall design based on a 10-year return period of 111,6819 mm. The results of the 10-year flood discharge analysis, with rational calculations for Jl. Pramuka Kanan at 0,879 m³/s, Jl. Pramuka Kiri at 0,949 m³/s, Jl. Jaksa Agung Suprapto Kanan at 0,662 m³/s, Jl. Suprapto Kiri at 0,722 m³/s, Jalan Bhayangkara Kanan at 0,520 m³/s, Jalan Bhayangkara Kiri at 0,654 m³/s, Jalan Kbp Duriyat Kanan at 0,574 m³/s, and Jalan Kbp Duriyat Kiri at 0,652 m³/s were observed. The calculation results indicate that the 10-year return period calculation discharge in the existing drainage channel exceeds the capacity, necessitating repairs. The repair was executed using U-Ditch 100 cm×100 cm for Jl. Pramuka Kanan, Jl. Pramuka Kiri, Jl. Jaksa Agung Suprapto Kanan, and Jl. Jaksa Agung Suprapto Kiri. In addition to the enhancements that have been made by utilising U-Ditch 80 cm×80 cm for Jl. Bhayangkara Kanan, Jl. Bhayangkara Kiri, Jl. KBP Duriyat Kanan and Jl. KBP Duriyat Kiri, further developments are anticipated.